BIOM-25. IDENTIFYING EXTRACELLULAR VESICLES FROM GLIOBLASTOMA OR NON-NEOPLASTIC CELLS VIA IMAGING FLOW CYTOMETRY. (9th November 2020) - Milbeth Cumba Garcia, Luz; Aibaidula, Abudumijiti; Kazemi, Nazanin Yeganeh; Jung, Miyeon; Lucien-Matteoni, Fabrice; Markovic, Svetomir; Parney, Ian
Abstract: Patients with glioblastoma (GBM) have a median survival of 15 months despite aggressive treatment. Immunosuppressive monocytes are heavily infiltrated in these tumors and in patients' circulation. Treatment-related pseudo-progression confounds outcome assessment by MRI. Thus, there is a need for additional non-invasive methods to assess treatment response. Extracellular vesicles (EVs) contain tumor-specific microRNA (miRNA) cargo that could serve as a liquid biopsy to distinguish true progression from treatment-related pseudo-progression. We had found significant differences in plasma EVs molecular profile (i.e. miRNA signatures) between GBM patients and healthy donors. Our overall hypothesis is that these differences reflect the EVs cell of origin. Our goal in this project was to develop a fluorescent staining paradigm by flow cytometry to distinguish EVs from different cells in vitro and determine differences in EV miRNA expression profile between GBM and monocytic cell-derived EVs. Gleolan (5-ALA) is an FDA-approved orally available agent for fluorescence-guided resection of GBM tumors. It is metabolized to protoporphyrin IX (PpIX) in GBM cells but not in non-neoplastic cells and has been reported to aid in the detection of GBM-derived EVs by flow cytometry. However, distinguishing between GBM-derived EVs and EVs from other cells of origin has not been described. We co-cultured human GBM cells (dBT114 or dBT116) and CD14+ monocytes for 72 hours in the presence or absence of 5-ALA. EVs were isolated by ultracentrifugation and stained for CD11b (myeloid cell marker). ImageStream Imaging Flow Cytometry was performed showing clear differentiation between PpIX+ EVs from GBM cells and CD11b+ EVs from monocytes. Interestingly, a small number of double-positive EVs (presumably representing monocyte-derived EVs that had taken up PpIX after phagocytizing GBM cells) were also present. Taken together, we were able to optimize a technique to distinguish EVs originating from GBM and monocytes for further characterization by short non-coding RNA sequencing.